Pertanggungjawaban Keuangan Daerah Dalam Rangka Kunjungan Kerja Dewan Perwakilan Rakyat Daerah - Mukhamad Iqom Difaul Khaq (Lex Renaissance, 2022)
The purpose of the research is to examine the mechanism for implementing the use of regional finances in the framework of the working visit of the Regional House of Representatives (DPRD) of Pekalongan City in 2014 and the accountability of the implementation of the use of regional finances in the framework of the working visit of the DPRD of Pekalongan City according to Law Number 23 of 2014 on Regional Government. This research uses normative research methods supported by empirical studies. The results of the study conclude that first, the mechanism for implementing the use of regional finance in the context of a working visit to the DPRD of Pekalongan City is not based on the provisions according to Law Number 23 of 2014. The inaccuracy in the implementation is evidenced by the report on the results of the examination of the Central Java BPK RI LKPD 2016 Number 55C/LHP. /BPK/XVIII.SMG/05/2017 dated May 22, 2017. Second, the accountability for the implementation of the use of regional finances in the framework of the working visit of the DPRD of Pekalongan City is not based on Law Number 23 of 2014 on Regional Government. Members of the DPRD of Pekalongan City as the executor of the activity did not fully make the accountability document in accordance with the actual reality. The DPRD Secretary, PPTK, and the Expenditure Treasurer at the DPRD Secretariat are not careful in controlling and verifying the evidence of accountability for the Work Visit activities of Leaders and DPRD members outside the region.Key Words: Accountability; regional finance; work visit; regional people's representative assembly AbstrakTujuan penelitian yakni untuk mengkaji mekanisme pelaksanaan penggunaan keuangan daerah dalam rangka kunjungan kerja Dewan Perwakilan Rakyat Daerah (DPRD) Kota Pekalongan 2014 dan pertanggungjawaban pelaksanaan penggunaan keuangan daerah dalam rangka kunjungan kerja DPRD Kota Pekalongan menurut Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Penelitian ini menggunakan metode penelitian normatif yang dengan didukung studi empiris. Hasil penelitian menyimpulkan bahwa pertama, mekanisme pelaksanaan penggunaan keuangan daerah dalam rangka kunjungan kerja DPRD Kota Pekalongan tidak berdasarkan ketentuan menurut Undang-Undang Nomor 23 Tahun 2014. Ketidakcermatan dalam pelaksanaan tersebut dibuktikan dengan laporan hasil pemeriksaan BPK RI Jawa Tengah LKPD Tahun 2016 Nomor 55C/LHP/BPK/XVIII.SMG/05/2017 Tanggal 22 Mei 2017. Kedua, pertanggungjawaban pelaksanaan penggunaan keuangan daerah dalam rangka kunjungan kerja DPRD Kota Pekalongan tidak berdasarkan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Anggota DPRD Kota Pekalongan selaku pelaksana kegiatan tidak sepenuhnya membuat dokumen pertanggungjawaban sesuai dengan kenyataan sebenarnya. Sekretaris DPRD, PPTK, dan Bendahara Pengeluaran pada Sekretariat DPRD tidak cermat dalam melakukan pengendalian dan verifikasi atas bukti pertanggungjawaban kegiatan Kunjungan Kerja Pimpinan dan anggota DPRD luar daerah. Kata-kata Kunci: Pertanggungjawaban; keuangan daerah; kunjungan kerja; dewan perwakilan rakyat daerah